Tunable Schottky Barrier and Interfacial Electronic Properties in Graphene/ZnSe Heterostructures - Xiao, Wenjun; Liu, Tianyun; Zhang, Yuefei; Zhong, Zhen; Zhang, Xinwei; Luo, Zijiang; Lv, Bing; Zhou, Xun; Zhang, Zhaocai; Liu, Xuefei (Frontiers in Chemistry, 2021)
With a direct bandgap, two-dimensional (2D) ZnSe is a promising semiconductor material in photoelectric device fields. In this work, based on first-principles methods, we theoretically studied the modulation of the Schottky barrier height (SBH) by applying horizontal and vertical strains on graphene/ZnSe heterojunction. The results show that the inherent electronic properties of graphene and ZnSe monolayers are both well-conserved because of the weak van der Waals (vdW) forces between two sublayers. Under horizontal strain condition, the n(p)-type SBH decreases from 0.56 (1.62) eV to 0.21 (0.78) eV. By changing the interlayer distance in the range of 2.8 Å to 4.4 Å, the n(p)-type SBH decreases (increases) from 0.88 (0.98) eV to 0.21 (1.76) eV. These findings prove the SBH of the heterojunction to be tuned effectively, which is of great significance to optoelectronic devices, especially in graphene/ZnSe-based nano-electronic and optoelectronic devices.